Soil Nutrients Influence Plant Community Assembly in Two Tropical Coastal Secondary Forests. (December 2018) - Long, Cheng; Yang, Xiaobo; Long, Wenxing; Li, Donghai; Zhou, Wei; Zhang, Hui
Understanding the responses of species diversity and dominant species to soil nutrient dynamics can enhance our knowledge of species coexistence and the recovery of secondary forests. Here, we assessed how species diversity and the abundance of dominant species varied as a function of soil nutrients at early- and mid-successional stages in two tropical monsoon coastal secondary forests in southern China. Results showed that species diversity was higher in the mid-successional stage. Species diversity was significantly correlated with organic matter and available P in both stages. The abundance of dominant species was significantly associated with organic matter, K, P, and N. Soil nutrients are therefore likely to play vitally important roles in the successional trajectory and restoration of these tropical coastal secondary forests.